The Effects of Unemployment, Management of Zakat Funds, and Economic Expansion on Poverty - Alam, Azhar; Suratman, Asyifa Syauqi; Setyowati, Eni (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2023)
This study aims to determine whether there is an impact of unemployment, management of zakat funds, and economic growth on poverty. With data sources from the Central Statistics Agency and BAZNAS from 2015-2020, the study used Ordinary Least Square (OLS) regression analysis to test the effect of independent variables on dependent variables. The results of this study show that zakat has a significant negative influence on poverty rates. Unemployment in this study shows its considerable effect on poverty. Meanwhile, economic growth has no significant impact on the poverty rate. The findings recommend that the government evaluate economic growth that the poor still need to enjoy fully. This research is also expected to pave the way for the community to know the role of zakat and economic growth in helping fellow human beings and also helping the country. The government can also contribute to increasing community socialisation about the impact of zakat on the country.